PERAN PENDIDIKAN AGAMA ISLAM DALAM MEMBANGUN KARAKTER MORAL PELAJAR DI ERA MODERN - Pitoyo, Pitoyo; Safi’ul Wahida; Ajeng Kamaratih; Muhammad Galang Pramudya; Anthon Setio Budi; Prayitno (Al Fattah Ejournal Sma Al Muhammad Cepu, 2024)
The aim of this research is to find out how Islamic Agma education contributes to the formation of students' moral character today. An effective Islamic religious education system in schools is expected to help build good moral character and encourage students to apply the values contained in the main material taught by teachers. The research method is a qualitative literature study collected through the literacy process of various books, articles and journals related to the research topic. One conclusion that can be drawn from the role of Islamic religious education in building students' moral character in the modern era is that a new breakthrough system is needed in terms of teaching and the material taught. If this system is created well, students will easily accept what educators teach.